(untitled) (Revista INTEREDU11, 2022)
This article seeks to problematize the subjectivity that arises in the formation of young people from the establishment of the Integral Education Program and the emergence of the Life Project, which seeks to explore youth protagonism as a “discipline” that guarantees autonomy to students, allowing them to gradually meet the needs of the contemporary world and their relations with the world of work, in the development of skills that allow people to train as an autonomous, supportive, and competent person, and to continue learning throughout life. Starting from the premise “learning to learn” or “learning for life”, we question the premises of this Life Project, observing them in the field of neoliberalism, as defended by Michel Foucault (2010) and Dardot and Laval (2016), since it acts as a mode of behavior, as a new reason for the world, producing the necessary subjects for its functioning. In this manner, we talk about a subject who assumes the protagonism of its own life, as an entrepreneur of its own self.